Congenital sideroblastic anemia in a child with biliary atresia: An association? - Ashish S. Patil; Nalla Anuraag Reddy; Harsha Prasada Lashkari (Elsevier, 2023)
Background: Congenital sideroblastic anemias (CSAs) are a rare inherited group of anemias. They are usually syndromic with neuromuscular and metabolic phenotypes. We report a child with sideroblastic anemia with the rare association of extrahepatic biliary atresia (EHBA). Case report: A two-and-a-half-year-old boy was diagnosed with EHBA at 2 months of age and underwent Kasai's procedure. He had failure to thrive and global developmental delay on follow-up. He presented with fever, hepatosplenomegaly, and pancytopenia at 1.5 years of age. Viral assays were negative, and bone marrow aspirate was hypercellular with trilineage hematopoiesis. Suspecting an association between pancytopenia, hypersplenism, and EHBA, whole exome sequencing was performed, which revealed a homozygous pathogenic autosomal recessive variant (p.GLU311ArgfsTer81) of PUS1(+) gene on exon 5. He was managed with regular packed red cell transfusions and oral pyridoxine. He is doing well with reduced transfusion requirements. Conclusions: We report a rare association/co-occurrence between CSA and EHBA, which is not reported so far. Similar reports in the future may help in ascertaining this phenotypic association.